The adoption of cloud computing in autonomous vehicle - Vasudavan, Hemalata; Shanmugam, Kamalanathan; Abdilaziz Ahmada, Harith (International Journal of Engineering and Technology, 2018)
Cloud computing is a popular disruptive technology that has been pervasively spread around the globe and becoming part of our daily life. Leveraging the ubiquitous nature of cloud platforms, can be value adding approach to the massive data acquired from autonomous vehicles. The data extracted from autonomous vehicleâ€™s sensors and actuators, together with other embedded smart devices can be monetized using cloud platforms to enhance reliability, comfort and improve security while driving. This paper focuses on the adoption of the cloud compu-ting in autonomous vehicles. Using Technology Acceptance Model (TAM) and Diffusions of Innovation (DOI), a new conceptual framework is extended to investigate and analyze factors underpinning the adoption.Â Â Â